THE COMMUNITY DEVELOPMENT OF SANGKARRANG OCEAN DIVE GROUP THROUGH CORAL STOCK CENTER AND CORAL TRANSPLANTATION AT BARRANG LOMPO ISLAND - Fathuddin Fathuddin; Rahmat Januar Noor; Muhammad Imran Lapong; Andi Ramlan; Ardy Ardy; Syahrul Harijo (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat ITB Nobel Indonesia, 2022)
The coastal waters of Barrang Lompo Island have suffered severe damage to coral reefs so that the islanders no longer benefit from the existence of coral reef ecosystems. Based on these conditions, this program aimed to improve the conditions of coral reef ecosystems through the coral stock center, coral transplants, and the promotion of education-based tourism programs. The implementing method of the activity is through technical guidance, procurement of vertical artificial reef installations, procurement of the spider model coral transplantation, and promotion of marine tourism education programs through social media and websites. The results of the program impact analysis showed that the coral stock center supported the concept of marine education tourism where the interest of tourists to visit Barrang Lompo Island is increasing and gives a multiplier effect for partners, such as an increase the partnership, the economic conditions, increase in partner knowledge and competence related to coral reef ecosystems, and diving skills license.